METODOLOGIA DE ANÁLISE DE INDÍCIOS ECONÔMICOS DE CARTEL NO SEGMENTO DE REVENDA VAREJISTA DE COMBUSTÍVEIS: O MERCADO DE GASOLINA COMUM EM SALVADOR - Costa, Cleber Ribeiro da Silva (2011)
The present work has as its theme the methodology of economic analysis of evidence of a cartel in the sector of retail fuel retailer: the market for gasoline in Salvador. The objective is to evaluate the methodology currently adopted by the ANP is the best way to identify economic evidence of a cartel in the sector of retail fuel retailer. Thus, the present work the following objectives: a) review the methodology currently adopted by the ANP to identify economic evidence of a cartel in the sector of retail fuel retailer b) present the DECC as a database monitoring to detect evidence economic cartel in the sector, with emphasis on regulatory proposals to adapt the DECC for the application of georeferencing, providing better monitoring and enforcement process to be executed by the ANP and other government institutions, and c) present the methodology of georeferencing as a superior alternative to methodology currently adopted by the ANP, as it allows a better definition of the relevant market for the detection of cartels in the retail segment of retail fuel. It was found that, in strictly economic point of view, there is evidence of agreement among the retail dealers in Salvador to earn profit margins above competitive levels. The hypothesis was confirmed using the georeferencing, a view that shows a better definition of the relevant market in the economic analysis of evidence of a cartel in contrast to the analysis conducted by the ANP, which currently takes into account the municipality as a whole. In order to address the adequacy of the price data currently available, the DECC is presented as a new database for the analysis conducted by the ANP, which should be improved by including data from the geographical location of retail dealers, including Data of the cost of retail dealers to ascertain possible impacts of any increased costs in the prices of resale and the data of the exact moment of change in prices. With that, authorities will have a necessary analytical tools to determine the temporality of changes in prices, and may establish in the administrative investigation and criminal responsibilities of each retail dealer, embodied by physical evidence derived from a further investigation. We also conclude that the DECC will bring greater efficiency for the supervision and monitoring of the fuel market, with the adoption of automated procedures to increase intelligence information to be generated in order to deter fraud. It was suggested that to be adopted within the routines inherent to the DECC, because it is information provided declaratory in character, the data to be cross-checked by the current database of the ANP and by agreement with the Internal Revenue Service of Brazil, to confront the data sent to the Electronic Invoice, and make standard audit work to be performed by servers embedded in the task of monitoring in the field, to be of fundamental importance for the validation of data.